Genetic model and exploration target area of geothermal resources in Hongtang Area, Xiamen, China - Chun-lei Liu; Chen-ming Lu; Ya-song Li; Qi-chen Hao; Sheng-wei Cao (Journal of Groundwater Science and Engineering, 2022)
The geothermal resources in Fujian Province are mainly hydrothermal resources of medium-low temperature. To better understand the whole process and conditions of heat control in the middle and deep crust, this study focuses on the analysis of heat accumulation model in Hongtang Area of Xiamen, and the main conditions of the model such as faults and sags are explored and interpreted in detail by using gravity and wide-field electromagnetic methods. 4 main faults (F33, F2, F12 and HT-F1) and 10 secondary faults (HT-F2, HT-F3, HT-F4, HT-F5, HT-F6, HT-F7, HT-F8, HT-F9, HT-F10 and HT-F11) were inferred, and the distribution range of sags was delineated. The convective geothermal system is composed of four components: Heat source, geothermal reservoir, heat-conductive fault and heat retaining cover, which form a quaternary heat accumulation model. According to the model, the intersection of the main faults F12, HT-F1 and F33 can be delineated as the primary target area of geothermal exploration, while the intersection of the secondary faults (F12 and HT-F6; F12 and HT-F2; HT-F9, HT-F10 and F12; F12 and HT-F11; F33 and HT-F3; HT-F8 and HT-F3; HT-F2, HT-F10 and HT-F1) can be delineated as the secondary target area. Borehole DR01, which is located in the primary target area, shows that the water temperature increases from fast to slow in the depth range of 0–500 m, and stays at 36℃ below 500 m. The reliability of the heat accumulation model and the target area was tested via geothermal boreholes, which is of great significance to the exploitation and utilization of geothermal resources in Hongtang Area of Xiamen.